2018
DOI: 10.3390/horticulturae4040042
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Knowledge, Perception and Practices in Apple Pest Management and Climate Change in the Fes-Meknes Region, Morocco

Abstract: Apple production in the Fes-Meknes region of Morocco is highly affected by pests and adverse weather conditions. A survey of apple farmers’ knowledge, perceptions and practices (KPP) in pest management and climate change was conducted in spring 2018 in two major apple-producing provinces of the region. Each farmer reported three insect pests and two diseases on average affecting their orchards. Pest management was performed by a combination of cultural and chemical methods. All farmers used dormant chemical sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Consequently, some management practices should be implemented by the government and farmers, including developing a protocol for visual inspection of RPW infestation; establishing a quick, reliable, cost-effective, and easily applicable early detection device or technique for RPW infestation; and conducting a risk assessment of the area using both visual observation and pheromone traps [25]. This result is aligned with other studies [20,30,53,54] that have reported a positive relationship between knowledge of symptoms and IPM adoption for various pests.…”
Section: Discussionsupporting
confidence: 74%
“…Consequently, some management practices should be implemented by the government and farmers, including developing a protocol for visual inspection of RPW infestation; establishing a quick, reliable, cost-effective, and easily applicable early detection device or technique for RPW infestation; and conducting a risk assessment of the area using both visual observation and pheromone traps [25]. This result is aligned with other studies [20,30,53,54] that have reported a positive relationship between knowledge of symptoms and IPM adoption for various pests.…”
Section: Discussionsupporting
confidence: 74%
“…Despite the reliance and high usage of synthetic pesticides, the respondents showed a poor understanding in the modes of action (MOA) of different pesticides ( As a result, the farmers were merely be switching pesticides with the same MOA of different trade names (Moinina et al, 2018). In addition, farmers with low literacy or without formal agriculture education may find the information of MOA difficult to understand, and often refer to advice from licensed pesticide dealers.…”
Section: Knowledge Level Of the Respondents On Ipmmentioning
confidence: 99%
“…In addition to protective fungicides, apple farmers in Morocco rely on three classes of systemic fungicides, namely, methyl benzimidazole carbamate (MBC) fungicides, demethylation inhibitors (DMIs) and the quinone-outside inhibitors (QoI). The three most widely used systemic fungicides that belong to these classes are thiophanatemethyl, difenoconazole and trifloxystrobin, respectively (Moinina et al, 2018). Precisely, we used the three aforementioned active ingredients.…”
Section: Choice Of Fungicidesmentioning
confidence: 99%
“…Out of about twenty cultivars of apples grown in Morocco, 'Golden Delicious' occupies up to 50% of the surface area, followed by 'Starking Delicious' (14%) and about 5% of 'Gala' cultivar (MADRPM, 2014). Management of apple scab disease is expensive due to the high number of fungicide applications (12 to 20) (Oukabli, 2004;Moinina et al, 2018). In order to prevent the development of fungicide resistance in the pathogen population, a farmer needs to reduce fungicide sprays per season and alternate fungicides with different modes of action (MoA).…”
Section: Introductionmentioning
confidence: 99%